ANALISIS PENINGKATAN KESEMPATAN KERJA DI INDONESIA - sunartono, sunartono (Badan Pengkajian dan Penerapan Teknologi, 2008)
The problems of labor have influenced of many factors as such global market,regulation and goverment policy. Indicators of labor that a number used up till now were considered have some weakness. The result of this analysis was indicated the presents of sector performance variation and labor change viewed according to economic sectors. The demographic pressure to labor supply can be describe that population grow 1,7 percent per year at 2000-2005 period. Estimated the number higher that population grow of the time 2000-2005 is 1,3 percent per year and 2005-2009 is 1,1 percent per year. Many labor policy can be implemented to development and improve the skill and knowledge. A lot of the labor problems is multidimention properties can be solve by multidimention approaches. A number of external and internal factors of labor were also showed the various effect based on the many sectors. Therefore, to improve capacity of each sector will be needed policy intervention which to take care of the such as variation.